2006
DOI: 10.1021/bi060642k
|View full text |Cite
|
Sign up to set email alerts
|

Cation Binding in Na,K-ATPase, Investigated by 205Tl Solid-State NMR Spectroscopy

Abstract: Cation binding to Na,K-ATPase is characterized in native membranes at room temperature by solid-state NMR spectroscopy using the K(+) congener (205)Tl. It has been demonstrated that the signals from occluded Tl(+) and nonspecifically bound Tl(+) can be detected and distinguished by NMR. Effects of dipole-dipole coupling between (1)H and (205)Tl in the occlusion sites show that the ions are rigidly bound, rather than just occluded. Furthermore, a low chemical shift suggests occlusion site geometries with a rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…A low chemical shift also suggested that occlusion site geometries have a relatively small contribution from carboxylate and hydroxyl groups. The non-specific binding of thallium ions were characterised by rapid chemical exchange, in agreement with an observed low binding affinity [363].…”
Section: Thalliumsupporting
confidence: 74%
“…A low chemical shift also suggested that occlusion site geometries have a relatively small contribution from carboxylate and hydroxyl groups. The non-specific binding of thallium ions were characterised by rapid chemical exchange, in agreement with an observed low binding affinity [363].…”
Section: Thalliumsupporting
confidence: 74%
“…It is possible that the errors in the determination of Tl 1 bound at high concentrations in the filter experiments obscure the nonspecific component. Using the data for nonspecific binding to shark enzyme from Jakobsen et al (35), we estimate this to be ;2.5 nmol/mg at 30 mM Tl 1 , which corresponds to almost one Tl 1 per nucleotide binding site. To within experimental uncertainty, the Tl 1 occlusion capacity in the presence of 50% glycerol or 20% PEG is similar to that of the control enzyme, but precision is severely limited by the differential retention of the protein on the filters.…”
Section: Tl 1 Binding At Equilibriummentioning
confidence: 96%
“…We have previously observed ;2 Tl 1 ions occluded per nucleotide site by using a centrifugation technique, which allows a larger range of Tl 1 concentrations to be tested. But in addition, the data indicated a large nonspecific low-affinity binding of Tl 1 to the membranes (28,35). It is possible that the errors in the determination of Tl 1 bound at high concentrations in the filter experiments obscure the nonspecific component.…”
Section: Tl 1 Binding At Equilibriummentioning
confidence: 99%
“…Tl + cannot be regarded as a perfect K + ‐analogue, but a large number of studies in very different fields indicate that it mimics K + quite well. Tl + can replace, for instance, K + in studies of K + ‐binding to the Na,K‐ATPase (Jakobsen et al. 2006) or K + ‐binding to nucleic acids (Gill et al.…”
Section: Discussionmentioning
confidence: 99%